The Influence of Store Atmosphere, Location, and Price Perception on Purchase Decisions (Study on Arabeauty Stores, Ternate City) - Wakano, Raidah Adinda; Mahungo, Yolanda; Buamonabot, Irfandi (AIBPM Publisher, 2024)
This study aims to determine whether the store's mood, location, and perceived pricing have an impact on consumers' decisions to buy. Data collection uses basic information obtained from questionnaires. All people who participated in this study were consumers of Arabeauty stores in Ternate City. There are 119 responders in the study's sample. PLS-SEM is the testing tool. The findings largely indicate that the location variable has no bearing on the decision to buy, the business atmosphere variable influences the decision to buy, and the pricing perception variable influences the decision to buy